The deadly bite of Salmonella Typhi. (22nd June 2015) - Zhang, Kaiyi; Hornef, Mathias; Fulde, Marcus
<x xml:space="preserve">Abstract</x> Pathogenic microorganisms overcome the host's innate and adaptive immune system and cause local or systemic infections, potentially leading to organ failure, sepsis, or even death. Some microorganisms can also directly or indirectly alter the differentiation and proliferation of host cells, promoting the development of tumors. A large number of oncogenic viruses have been identified and estimated to account for 15% of human cancers. They do so by encoding oncogenes or through their intrinsic ability to manipulate the genomic stability of the host cell by integrating their own genetic elements. Also bacterial infections have been linked to carcinogenesis, although the underlying molecular mechanisms are less well understood. The best‐studied example is Helicobacter pylori, which has been classified as a class I carcinogen by the World Health Organization due to its ability to promote stomach cancer after chronic infection, which causes tissue inflammation and atrophy of the gastric mucosa. In a recent issue of Cell Host & Microbe, the Neefjes laboratory explores the association between Salmonella enterica subsp. enterica sv. Typhi (S. Typhi)—which is the causative agent of human typhoid fever—and gallbladder carcinoma 1.